Hypocreadium toombo n. sp. (Digenea: Lepocreadiidae) in the yellow-spotted triggerfish Pseudobalistes fuscus (Perciformes: Balistidae) and additional lepocreadiids parasitizing fishes from the waters off New Caledonia - Bray, Rodney A.; Justine, Jean-Lou (Zootaxa, 2006)
Hypocreadium toombo n. sp. is described from the balistid Pseudobalistes fuscus from the waters off New Caledonia. It is distinguished by a series of characters shared by no other Hypocreadium species. The specimens are always slightly longer than wide, have a distinct anterior notch, have the vitelline fields confluent or nearly so in the forebody and have the terminal ends of the caeca pointing anteriorly. Other lepocreadiid species also recorded from New Caledonian waters are Lobatocreadium exiguum from P. fuscus, Intusatrium robustum from Bodianus perditio and B. loxozonus, Postlepidapedon secundum from Choerodon graphicus and Lepidapedoides angustus from Epinephelus fasciatus.